Induction of the insulin proreceptor by hydrocortisone in cultured lymphocytes (IM-9 line). - Rouiller, D G; McElduff, A; Hedo, J A; Gorden, P (The Journal of Clinical Investigation, 1985)
Hydrocortisone increases the number of insulin receptors at the surface of human cultured lymphocytes (IM-9 line) without altering the degradation of the mature receptor subunits. To elucidate the effect of glucocorticoids on the biosynthesis of the insulin receptor of IM-9 cells, we preincubated cells in the presence or absence of hydrocortisone (1.4 X 10(-6) M) and measured the incorporation of radiolabeled sugars into the insulin receptor components. From 6 to 22 h, there was a progressive increase in the incorporation of [3H]mannose into the insulin proreceptor (190,000 mol wt) and the mature subunits (210,000, 135,000, and 95,000 mol wt). The amount incorporated into hydrocortisone-treated cells was always three to four times higher than in control cells, despite no change in cell number, viability, or radioactive sugar pool. To test directly the earliest effect of hydrocortisone, we undertook pulse-chase studies. The incorporation of [3H]mannose into the insulin receptor precursor and the mature subunits was detectable as early as 30 min of chase and was two to three times higher in hydrocortisone-treated cells at any time point of incubation. In both groups, the increase into the proreceptor (190,000 mol wt) peaked by 60 min and decreased rapidly thereafter (half disappearance rate, 45 min); there was a sustained increase of incorporation into the two major mature subunits (135,000 and 95,000 mol wt) throughout the 4-h chase. Hydrocortisone represents the first pharmacologic agent shown to induce the synthesis of the insulin proreceptor. Further, we present a model system designed to study other agents that may act at a very early step in insulin receptor biosynthesis. Images